Pemberian Kombinasi Jus Bayam Dan Tomat (Studi Kasus Anemia Dalam Kehamilan) - Siti Yuliana; Endang Pertiwiwati (School of Nursing, Faculty of Medicine and Health Science, Lambung Mangkurat University., 2021)
Iron anemia in pregnancy, where the Hb (hemoglobin) level is <11 g / dL in the first and third trimesters and <10.5 g / dL in the second trimester. Efforts to increase hemoglobin levels for pregnant women can be done with complementary therapies using a combination of spinach and tomato juice. The purpose of this study was to determine the effect of giving nursing care to Mrs. M with anemia in the third trimester of pregnancy through the intervention of a combination of spinach and tomato juice.